Keadaban Dalam Tradisi Mameugang Masyarakat Aceh - Iskandar Iskandar (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
Mameugang tradition in Acehnese society has been started since the sultanate of Aceh. The day of Mameugang tradition, Acehnese droves to buy meat to welcome the month of Ramadan, id fitri and id adha. This activity continued every year for generations. The behavior of the tradition has formed a special pattern of the Acehnese people in consuming meat. This paper is excerpted from the results of field research that elaborates on the meaning and traditions callebrations of civility in mameugang. This research uses a qualitative method where the researcher serves as the research instrument. Primary data obtained from interviews and secondary data from the literature related records. Research was conducted in Lhoksumawe and Aceh Utara. In the end, this research reveals that the celebration mameugang for the Acehnese as an expression of gratitude and respect towards Ramadhan. Mameugang tradition also as a means silaturrahmi with relatives. While the value contained in mameugang tradition is “ta’awun, lita’limi and meubalah or syakur”. So factors that influence the behavior of private consumption in celebration of mameugang are socio-cultural values, politics and religion.